IDIOPATHIC TROMBOCYTOPENIC PURPURA DURING PREGNANCY.OBSTETRICS AND PERENATAL RISKS - V. B. Tskhay; E. K. Grebennikova (Акушерство, гинекология и репродукция)
Idiopathic thrombocytopenic purpura is a relatively rare disease, especially during pregnancy. Currently, there are many ways of diagnostics, monitoring and treatment of patients. Pregnant women with idiopathic thrombocytopenic purpura are at risk of hemorrhagic complications during pregnancy and postpartum period; moreover, they may give birth to infants with severe thrombocytopenia. Specialists widely discuss obstetric and perinatal risks in this disease, the risk of ante- and intranatal intracranial hemorrhage in newborns. In this review we have assessed the risks of obstetric and perinatal outcomes with different methods of delivery as well as the effectiveness of therapeutic interventions in pregnant women with idiopathic thrombocytopenic purpura.